In vivo swine kidney viscoelasticity during acute gradual decrease in renal blood flow: pilot study (2013)
Elasticity imaging methods have been used to study kidney mechanical properties and have demonstrated that the kidney elastic modulus increases with disease state. However, studies in swine suggest that kidney elastic modulus is also affected by hemodynamic variables. A newly emerging method called Shearwave Dispersion Ultrasound Vibrometry (SDUV) offers a tool to determine renal elasticity and viscosity in vivo. The purpose of this study was directed toward evaluating the feasibility of SDUV for in vivo measurements of healthy swine kidney during acute gradual decease of renal blood flow. In this study in vivo SDUV measurements were made on a group of 5 normal swine kidneys at baseline renal blood flow (RBF) and 25, 50, 75 and 100% decrease in RBF. The shear elastic modulus at full baseline was 7.04 ± 0.92 kPa and 3.48 ± 0.20 kPa at 100% decrease in RBF. The viscosity did not change between baseline (2.23 ± 0.33 Pa•s) and 100% decrease in RBF (2.03 ± 0.32 Pa•s). The data from this study indicates that other variables such as local blood flow, pressure and volume as well as method accuracy need to be measured to illustrate the relationship between shear elasticity and viscosity associated with acute kidney processes.